BASE METAL - PLATINUM-GROUP ELEMENT SULFIDES FROM THE URALS AND THE EASTERN ALPS: CHARACTERIZATION AND SIGNIFICANCE FOR MINERAL SYSTEMATICS - Melcher F. (My University, 2000)
A mineralogical classification of sulfides containing base metals (BM) and platinum group elements (PGE) is proposed based on BM-PGE ratios. Group A comprises BM sulfides carrying PGE as trace or minor elements (e.g., pentlandite). Group B is characterized by BM/PGE > 1 comprising kharaelakhite and some poorly defined minerals (thiospinels and monosulfides) which are described in detail. In group C, all sulfides with BM/PGE<1 are summarized, comprising PGE-rich thiospinel, minerals related to the thiospinel group (e.g. xingzhongite, konderite, inaglyite), and the Pd-Pt±Ni sulfides. A number of BM-PGE sulfides are described from podiform chromite occurrences in ultramafic portions of ophiolite complexes in the southern Urals (Kempirsai, Kazakhstan) and the Eastern Alps (Kraubath, Austria). Copper- and (Ir, Rh, Pt)-rich thiospinel (general formula AB2S4, with A=Cu, Ni, Fe and B=Ir, Rh, Pt) is present in complex assemblages in Kraubath, usually intergrown with laurite, Pt-Fe alloy and Rh sulfide. These thiospinels are commonly associated with lamellae and inclusions of Ni-and/or Fe-rich (Ir, Rh) sulfide showing either monosulfide or BM-rich thiospinel stoichiometry. In massive chromitite from Kempirsai, (Ni,Cu,Fe,Ir,Rh,Os) sulfides are intergrown with laurite-erlichmanite, Ir-Os alloy, and rarely, PGE sulfarsenides (e.g. irarsite), and usually have monosulfide (BM,PGE)S compositions. A small number of grains have (BM+PGE)/S matching PGE-rich thiospinel (cuproiridsite) and BM-rich thiospinel (Ni,Cu,Fe)1.5(Ir,Rh)1.5S4. In the occurrences studied, monosulfides exhibit sulfur-deficient stoichiometries (e.g., (BM,PGE)1−xS) and are characterized by BM/PGE ranging from 0.8 to 2.2. Although anisotropic in reflected light, their reflectance spectra (Y%=33–38) differ only slightly from those of isotropic cuproiridsite and cuprorhodsite (Y%=36–38). At least three groups of monosulfides can be distinguished on chemical grounds using literature data: monosulfides dominated by Ni and Ir (“iridian millerite”) with BM/PGE ranging from 1.6 to 5.9, monosulfides dominated by Fe and Rh (“rhodian pyrrhotite”) with BM/PGE ranging from 1.6 to 7.1, and monosulfides dominated by Cu, Ir or Rh (“xingzhongite”-type) with BM/PGE ranging from 0.6 to 1.1. While the first two types presumably crystallize in a hexagonal NiAs structure and exhibit extensive solid solution between each other, xingzhongite is cubic (BM-rich thiospinel?) and usually poor in Ni and Fe. Monosulfides and thiospinel may form from PGE-rich base metal sulfide liquids after cooling and equilibration in chromite-precipitating magmatic systems.